Ok let's take the information given and make an equations system with it.
I'm gonna use H for Hoang present working years and B for those of Bill. We know that right now Hoang has worked for 6 years longer than Bill, with this we can create the following equation:
![H=B+6](https://img.qammunity.org/2023/formulas/mathematics/college/zt6gl7u0wmuuemldwz5eimnzixg1r2r2hz.png)
We also have information from two years ago, at that time Hoang's working years doubled Bill's working years. One would feel tempted to write the equation H=2*B but you have to remember that this information is from the past and H and B stand for working years in the present. The correct way to approach this is change H and B by H-2 and B-2 so we consider that this information is from 2 years ago:
![\begin{gathered} (H-2)=2\cdot(B-2) \\ H-2=2B-4 \\ H-2B=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pl2yd58swfi95s5cpwc9e868kmxvt6dibp.png)
So now we have constructed our equations system:
![\begin{gathered} H=B+6 \\ H-2B=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m219fm0id00fgz8ndqc5g8b8tm99kkgevm.png)
Let's take the outcome of the first equation and use it in the second one:
![\begin{gathered} H-2B=(B+6)-2B=-2 \\ B-2B+6=-2 \\ -B=-2-6=-8 \\ B=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7oexai06ncgki7m874nw6t5bnaswzmu7en.png)
And going back to the first equation:
![H=8+6=14](https://img.qammunity.org/2023/formulas/mathematics/college/9f1mo1f6kbtcswnjca0ckq92pmznaa4dkt.png)
So Hoang has been working at the hospital for 14 years and Bill for 8 years.